2018
DOI: 10.1038/s41567-017-0024-5
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous topological insulators constructed from random point sets

Abstract: The discovery that the band structure of electronic insulators may be topologically non-trivial has revealed distinct phases of electronic matter with novel properties 1,2 . Recently, mechanical lattices have been found to have similarly rich structure in their phononic excitations 3,4 , giving rise to protected unidirectional edge modes [5][6][7] . In all of these cases, however, as well as in other topological metamaterials 3,8 , the underlying structure was finely tuned, be it through periodicity, quasi-per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
246
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(258 citation statements)
references
References 32 publications
4
246
0
Order By: Relevance
“…In the early 2010's, building on quantitative analogies with the topological phases of quantum matter, researchers laid out robust design rules for metamaterials supporting mechanical deformations immune from geometrical and material imperfections [2][3][4][5][6][7][8]. Today, mechanical analogs of virtually all topological phases of electronic matter have been experimentally realized, or theoretically designed, with mechanical components as simple as coupled gyroscopes or lego pegs [2,5,6,[9][10][11][12]. The basic strategy consists in connecting mechanical systems with gapped vibrational spectra having topologically distinct eigenspaces [8,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In the early 2010's, building on quantitative analogies with the topological phases of quantum matter, researchers laid out robust design rules for metamaterials supporting mechanical deformations immune from geometrical and material imperfections [2][3][4][5][6][7][8]. Today, mechanical analogs of virtually all topological phases of electronic matter have been experimentally realized, or theoretically designed, with mechanical components as simple as coupled gyroscopes or lego pegs [2,5,6,[9][10][11][12]. The basic strategy consists in connecting mechanical systems with gapped vibrational spectra having topologically distinct eigenspaces [8,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of gyroscopic metamaterials [11,13,14] showed that perturbations migrate to the edge of the sample and propagate around the edge in one direction. In our system, for very weak damping or small α m , it would be possible to perturb skyrmions in the bulk of the pinfree channel and obtain motion that is localized on the edges of the channel, producing a transient current which eventually damps away.…”
Section: Discussionmentioning
confidence: 99%
“…Another emerging topic is topological edge modes existing at the interface of two different amorphous materials. Recently, amorphous systems without time-reversal symmetry have been reported with unidirectional edge modes along the interface of two different amorphous bulks (35,36). It is natural, therefore, to further find topological transport between different amorphous structures without breaking time-reversal symmetry.…”
Section: Introductionmentioning
confidence: 99%